Chegou no Piauí, no Piauí tem tambor:as muitas faces do tambor de crioula piauiense na contemporaneidade - Oliveira, Maria Arthuane da Costa (2023)
This paper investigates the historical and identity construction of the cultural practice of tambor de crioula in the state of Piauí through the production of interviews with subjects who integrate the practice in the cities of Teresina - the state capital - and Porto, Cocais region. The spatial cut, although mainly focused on the present time, is delimited between the 1960s and the present day. The methodology applied in this study is based on the writings of Alessandro Portelli, Gayatri Chakravorty Spivak, Verena Alberti and Cléria Costa. The last author precisely guides the method of producing interviews that is based on the life history of each subject, are subsequently directed specific questions about the realization of the practice, their participation and perception about the manifestation. This work aims to perceive the different sides of the cultural practice of tambor de crioula and how these have been put by its players in the attribution of meanings and symbolisms and in the realization of the movement in the state of Piaui. It also discusses similarities and ruptures in the construction of the tambor de crioula practice between the municipalities mentioned above. Finally, this work presents an innovative analysis of the cultural practice of tambor de crioula in Piauí by researching the construction of this from the orality expressed among the practicing subjects. This reflects on how the practice has been carried out and passed on in the spaces that they circulate, being possible to perceive the mixture of traditional and innovative aspects that give rise to the understanding of the construction of the new sides of the practice.